Top answers

Maths
A Level

Do the circles with equations x^2 -2x + y^2 - 2y=7 and x^2 -10x + y^2 -8y=-37 touch and if so, in what way (tangent to each other? two point of intersection?)

We must first complete the square for both equations and get the equations in the (x-a)2+(y-b)2=r2 with the primary objective of determining the centres of both circles (a...

Answered by Shanti S. Maths tutor
2766 Views

How do you differentiate y=ln(x)

I would use the fact that ln is the inverse function of the exponential function e^x to re-write the equation as x=e^y. This can be directly seen by just putting e^y=e^(lnx). Since the definition of a ln(...

Answered by Milo G. Maths tutor
7289 Views

Find the area bounded by the curve y=(sin(x))^2 and the x-axis, between the points x=0 and x=pi/2

First, use the identity cos(2x)=(cos(x))^2-(sin(x))^2 along with the identity (sin(x))^2+(cos(x))^2=1 to obtain the integral of 1/2*(1-cos(2x)) as it is not possible to integrate (sin(x))^2 straight off w...

Answered by Thomas L. Maths tutor
3986 Views

Solve the simultaneous equations y = x^2 - 6x and 2y + x - 6 = 0

Rearrange the second equation in terms of y: meaning that the equation is of the form y = ....-this will give y = 3 - x/2You may now substitute the y in the left hand equation with what y in the right han...

Answered by Tabi D. Maths tutor
6298 Views

Express (4x)/(x^2-9) - (2)/(x+3) as a single fraction in its simplest form.

First we must expand the demoninator to; (x+3)(x-3)Then we can multiply the left hand fraction on top and bottom by (x-3) to get a common demoninatorthis gives us; (4x)/((x+3)(x-3)) - ((2)(x-3))/((x+3)(x-...

Answered by Eddie E. Maths tutor
3517 Views

We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences